Synthesis, Spectro Chemical Investigation of 4-Methyl Benzylamine Schiff Base Metal Complexes and Its Biological Studies: Pharmaceutical Science-Chemistry - Ramamohan, Gose; JayaRaju, A.; Soma Sekhar, A.; Nagaraju, N.; Pullanna, Y.C.; Sreeramulu, J. (International Journal of Life Science and Pharma Research, 2022)
Schiff bases and their complexes are versatile compounds synthesized from the condensation of an amino compound with carbonyl compounds and widely used for industrial purposes and also exhibit a broad range of biological activities including antifungal, antibacterial, anti-malarial, anti-proliferative, anti-inflammatory, antiviral, and antipyretic properties. Many Schiff base complexes show excellent catalytic activity in various reactions in the presence of moisture. Over the past few years, there have been many reports on their applications in homogeneous and heterogeneous catalysis. The influence of certain metals on the biological activity of these compounds and their intrinsic chemical interest as multidentate ligands has prompted a considerable increase in the study of their coordination behaviour. Development of a new chemotherapeutic Schiff bases and their metal complexes is now attracting the attention of medicinal chemists. Primary benzylamines are highly important building blocks in the pharmaceutical and polymer industry. The present paper deals with the synthesis and characterization of metal complexes of new Schiff bases derived from 4-Methyl Benzylamine. The bidentate ligand is derived from the inserted condensation of 4-Methyl Benzylamine with 2-hydroxybenzaldehyde (OHB) in a 1:1 molar ratio. Using this bidentate ligand, complexes of Zn (II), Cd (II) with general formula ML2 have been synthesized. The synthesized complexes were characterized by several techniques using IR, 1HNMR and Mass analysis. Infrared spectral data indicate the coordination between ligand and central metal ion through deprotonated phenolic oxygen and azomethine nitrogen. In addition, the authors have screened the compounds for biological activity. It was found that the compounds have shown activity against the organisms like Candida albicans, Bacillus subtilis and Salmonella typhi.